Superconducting properties of nanostructured microhelices. (21st August 2017) - Fomin, Vladimir M; Rezaev, Roman O; Levchenko, Evgenii A; Grimm, Daniel; Schmidt, Oliver G
Abstract: Superconducting micro- and nanohelices are proposed for the first time. A theoretical investigation of the superconducting state in the helical coils at the micro- and nanoscale is performed within the time-dependent Ginzburg–Landau approach. The pattern and number of vortices in a stationary distribution are determined by their confinement to the ultrathin helical coil and can therefore be efficiently controlled by the spiral stripe width and the spiral pitch distance for both dense and sparse coils. Quasi-degeneracy of vortex patterns is manifested in the helical coil when the number of vortices is incommensurable with the total number of half-turns. With increasing radius, superconducting helical coils provide a physical realization of a transition from the vortex pattern peculiar to an open tube to that of a planar stripe.